Telaah Historis Relasi Dialogis Agama-Agama Monoteis - Amir, Ahmad Nabil; Rahman, Tasnim Abdul (Al-Adyan: Journal of Religious Studies, 2024)
This article discusses the religious experiences of various faiths within the Abrahamic tradition. It first examines the underlying systems and approaches, as reflected in classical works of religious thought that outline meta-religious principles, methodologies, traditions, and ideological frameworks. In analyzing the history and traditions of Abrahamic beliefs, this article seeks to summarize them within the framework of comparative religion, highlighting their historical development and importance in inspiring convivencia (coexistence) in a global context. The analysis is based on classical works studying the science of religion (religionswissenschaft) and its methodologies, which have produced foundational approaches and principles in this field. The research uses a qualitative framework with descriptive and analytical methods. This article also examines modern developments in the field of comparative religious studies and its role in promoting interfaith dialogue, while exploring our shared human heritage that emphasizes the spirit of La Convivencia as an inclusive and pluralistic force, particularly in the Malay region. In summary, the findings of the article demonstrate the influence and unprecedented presence of the Abrahamic tradition’s seeds in the world’s religions, especially those of Semitic lineage.Artikel ini membahas pengalaman religius berbagai kepercayaan dalam tradisi Abrahamik. Pertama-tama kajian ini menyelidiki sistem dan pendekatan yang mendasarinya, sebagaimana tercermin dalam karya-karya klasik pemikiran religius yang menguraikan prinsip-prinsip meta-religius, metodologi, tradisi, dan kerangka ideologisnya. Dalam menganalisis sejarah dan tradisi kepercayaan Abrahamik, artikel berupaya merangkumnya dalam kerangka perbandingan agama, yang menunjukkan perkembangan historisnya serta pentingnya tradisi ini dalam menginspirasi convivencia (hidup bersama) dalam konteks global. Analisis dilakukan dengan mengacu pada karya-karya klasik yang mengkaji ilmu agama (religionswissenschaft) dan metodologi, yang melahirkan pendekatan serta prinsip-prinsip dasar dalam bidang ini. Penelitian menggunakan kerangka kualitatif dengan metode deskriptif dan analitis. Artikel juga mengkaji perkembangan modern dalam bidang studi agama perbandingan dan perannya dalam mempromosikan dialog antaragama, serta menggali warisan bersama kemanusiaan yang menyoroti semangat La Convivencia sebagai kekuatan inklusif dan pluralis, khususnya di kawasan Melayu. Secara ringkas, temuan dalam artikel ini menunjukkan pengaruh dan keberadaan benih tradisi Abrahamik sangat signifikan dalam agama-agama dunia, terutama dari garis keturunan Semitik, yang belum pernah terjadi sebelumnya.